Training of Rural Extension Agents in Latin America: Practices, Problems, and Proposals - Landini, Fernando (2022)
Introduction. Most academic work on training extension agents tends to address the topic tangentially, in a purely theoretical way or focussing on specific case studies. This article aims to describe, characterize, and analyze the training received by extension agents from Argentina, Chile, Cuba, Ecuador, Guatemala, and Uruguay. Method. A sample of 133 extension agents was interviewed in 68 individual and 18 group interviews. The interviews were transcribed and examined using content analysis with the support of Atlas.ti software. Results. Extension agents receive productive and methodological training, though they perceive the latter to be insufficient. Practical training and participatory methodologies, which allow for the exchange of experiences among peers, are valued the most. The interviewees recommend that extension institutions support their employees’ training and develop systematic training plans covering productive topics and extension methodologies. Training is expected to be practical, participatory, up-to-date, and sufficiently profound. Discussion. The research results concur with different investigations. The most important merit of the article is to analyze the situation in different countries beyond case studies. We recommend studying further the impact of institutional frameworks in the training practices for extension institutions.